Indonesian Canned Tuna Export in the Global Market - Daniel Bonartua Malau; Muhammad Rezaldi; Kashari; Jan Hotman (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
One of the biggest exporters of canned tuna worldwide is Indonesia. The purpose of this research is to examine the market dynamics and competitiveness of Indonesia's canned tuna exports (HS 160414) to important export markets between 2020 and 2024. This study uses a quantitative descriptive method with four analytical tools, which are Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA) Export Product Dynamics (EPD), and the X-Model Potential Export Product. Data were sourced from Trademap and the World Integrated Trade Solution (WITS). The results indicate that Indonesian canned tuna possesses a strong comparative advantage in nearly all destination countries, with RCA values >1 and positive RSCA values. Ecuador recorded the highest RCA value, while Egypt and Malaysia consistently lacked a comparative advantage. The EPD analysis placed South Korea, Oman, and Thailand in the Rising Star category as markets with the greatest potential. Based on the X-Model analysis, these three countries fall into the Optimistic Market Development category and are the top priorities for the development of Indonesian canned tuna exports. This study recommends strengthening market penetration strategies in high-potential countries as well as improving the quality and sustainability of fisheries resource management as the key to long-term competitiveness.